Polysemy and metaphor on zoomorphism in Lima colloquial Spanish speech - Gonzales Cavero, Rosario Mercedes (2022)
In this article are analyzed the linguistic expressions of the colloquial Spanish of Lima in which men and women are conceptualized as animals. It studies the polysemy and metaphor of the zoomorphisms cerdo, lobo, perro and zorro, and their respective feminine forms. This is a qualitative research with a descriptive scope. The cognitive mechanism of metaphor, the extended version of the Prototype Theory (Lakoff, 1980, 1987) and the Frame Theory (Fillmore, 1982) are used in the analysis, all of which allow the detailing of the cognitive and cultural motivations that condition a certain social group to express itself in that way. Finally, new senses were identified in each zoomorphism, showing that words are prone to variation, which is determined by the use of the speakers, especially among the younger generations.